Assessing bivalve growth using bio-energetic models - Tan, Tjui Yeuw [UNESP]; Miraldo, Marcel Câmara [UNESP]; Fontes, Roberto Fioravanti Carelli [UNESP]; Vannucchi, Fabio Stucchi [UNESP] (Elsevier, 2022)
Aquaculture can play a key role in providing sustainable and low-cost protein sources, with the potential to help particularly the socially and economically vulnerable population. Although many coastal populations already complement their diet by extracting wild brown mussels (Perna perna, Mytilidae) from the environment, an explicit assessment for mussel growth potential along the Brazilian coast has been conspicuously lacking. We provide a large-scale assessment for prospecting and developing mussel culture by applying a Dynamic Energy Budget (DEB) model coupled with remote sensing. We estimated DEB parameters for the P. perna Brazilian population and used satellite-derived yearly data was used as forcing variables, containing information of chlorophyll-a concentration as a proxy for food concentration, sea-surface temperature to modulate metabolic performance, and particulate organic carbon - discounted the contribution of chlorophyll-a - to take into account the negative effect of particles in the mussel ingestion rates. We then simulated mussel growth along a large region of the Brazilian coast and obtained the time it takes for the mussel to reach a 5 cm market-relevant length within each pixel as a means to visualize mapped mussel growth potential indicating the time it takes to reach commercial length. Our results highlight the regions where mussel growth can be relevant for supporting subsistence livelihoods and also for securing income for local communities by performing economic activities, as many of the identified regions do not yet have active mussel culture sites. We also show that mussels can be used for ecosystem services in regions where farming for human consumption is not advisable. Our study provides further evidence that bioenergetic models coupled with remote sensing allow for a pragmatic and cost-effective path to assess growth performance along large regions with implications for developmental policy and spatial planning.
Keywords: Aquaculture; Coastal planning; Dynamic energy budget; Food security; Mussel growth; Perna perna